A new species and a new combination of Sundamomum (Zingiberaceae) from Sarawak, Borneo - Salasiah, Mohamad; Meekiong, K.; Poulsen, Axel Dalberg (The Board of Trustees of the Royal Botanic Gardens, 2020)
A new ginger species, Sundamomum corrugatum from north east Sarawak is described. The species is easily recognised by its deeply corrugated leaves which at first glance might resemble Etlingera corrugata. The floral characters of the new species as well as of Amomum bungoense correspond well with the main characters circumscribing the genus Sundamomum, especially the anther crest, which is obscurely trilobed, but also by the coriaceous bract supporting a single flower, the pubescent inflorescence, the gullet-type labellum and their occurrence in the Sunda region. A detailed description and photographs of S. corrugatum are provided and the new combination of S. bungoense is made. Key Words. Amomum, Alpinieae, diversity, ginger, Malesia, taxonomy.